The Examples of Setting in The Eco-Fiction Novels by American Writer Mary Alice Monroe - Khayrullayeva Nigorabegim Ne’matillo kizi (International Journal on Integrated Education, 2023)
The relevance of the research. This article discusses how the setting of a literary work can alleviate an author's difficulties in describing time and space by allowing the reader to focus on the story's plot and characters. Because Mary Alice Monroe's work is ecological in nature, it has been described that the author skillfully depicts real places such as islands, beaches, mountains, fertile plantations, and other wildlife environments. In the article, the setting is mentioned as context beyond the immediate setting of the story. Settings include culture, era, geography, and time. Setting is considered the writer’s one of the basic building blocks of fiction, along with plot, characters, themes, and style. The objectives of the research. The article is aimed at to study the literary analysis of the setting and its functions in the eco-fiction novels “Time is a River”, “Sweetgrass”, “The Summer of Lost and Found” by American writer M.A.Monroe. We distinguish 5 functions of setting in these novels:1) Setting as a background for action; 2)Setting as an antagonist; 3)Setting as a means of creating appropriate atmosphere; 4)Setting as a means of revealing character; 5)Setting as a means of reinforcing the theme. Research methods. The method employed in this research is a semantic-stylistic analysis which aimed at identifying functions of setting since setting in fiction is called on to perform a number of desired functions. Conclusion. Setting features of Eco-fiction novel "Time" is a river”, “Sweetgrass”, “Lost summer” and examples from the study novel were reviewed. The aim of the author is to create a true world full of stories. For this to succeed, authors must remember that the basis of any literary work is the setting. The analysis of the setting of the work plays an important role. It improves the plot, characters, themes and even mood of the novel.